Socio-Economic Factors Influencing Household on Non-Timber Forest Product Dependency from Chilimo Forest, Ethiopia - Asfaw Gelan (CV. Literasi Indonesia, 2023)
Non-timber forest products are very important in providing basic needs, cash deposits, and home consumption to forest-adjacent communities. Several socio-economic factors influence household dependence on non-timber forest products. This study focused on analyzing the socio-economic factors determining a household’s dependency on non-timber forest products from the Chilimo forest in Dandi, Ethiopia. Descriptive statistics and logistic regression were applied to analyze the data. The main NTFPs extracted by local communities in the study area included honey, fodder, wild vegetables, medicinal plants, firewood, and charcoal. Thus products are used for home both consumption and commercial purposes. Availability of the non-timber forest product also influenced its extraction from the forest (χ2 (2,432) = 4.973, p<0.084). A majority of households (87%) who got NTFPs explained that this resource availability had decreased when compared to ten years ago, thus diminishing their chances of getting NTFPs possibly due to the degradation of the forest. Based on the results from logistic regression factors like age, the career of a household head, and distance to the market had a significant positive correlation on household NTFPs exploitation dependency. Household that lives near the forest has more advantages to extracting NTFPs from the forest than those who live further away. Also, land size, formal education, and household need for fuel wood were positively correlated with the local household, dependency on NTFPs from the Chilimo forest.